Electricity Generation by a Phototrophic Bacterium in a Glucose−Fed Double Chambered Microbial Fuel Cell Using a Fabricated 3D Anode Electrode - Aliyu, A. A.; Dahiru, R. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt